Harnessing the ubiquitin code to respond to environmental cues. Issue 2 (5th August 2022) - Orosa-Puente, Beatriz; Spoel, Steven H.
Abstract: Ubiquitination is an essential post-translational signal that allows cells to adapt and respond to environmental stimuli. Substrate modifications range from a single ubiquitin molecule to complex polyubiquitin chains, where diverse chain topologies constitute a code that is utilized to modify the functions of proteins in numerous cellular signalling pathways. Diverse ubiquitin chain topologies are generated by linking the C-terminus of ubiquitin to one of seven lysine residues or the N-terminal methionine 1 residue of the preceding ubiquitin. Cooperative action between a large array of E2 conjugating and E3 ligase enzymes supports the formation of not only homotypic ubiquitin chains but also heterotypic mixed or branched chains. This complex array of chain topologies is recognized by proteins containing linkage-specific ubiquitin-binding domains and regulates numerous cellular pathways. Although many functions of the ubiquitin code in plants remain unknown, recent work suggests that specific chain topologies are associated with particular molecular processes. Deciphering the ubiquitin code and how plants utilize it to cope with the changing environment is essential to understand the regulatory mechanisms that underpin myriad stress responses and establishment of environmental tolerance.